TINJAUAN MANAJEMEN EVENT PASA HARAU ART & CULTURE FESTIVAL DI KABUPATEN LIMA PULUH KOTA - Alfatah Haries; Fitri Wulandari (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2021)
This study aims to determine the Event Management of the Pasa Harau Art & Culture Festival. The data analysis method used in this research was a descriptive method. The data collection techniques were observation, interviews, documentation and literature review The results of this study concluded that in event management there are five important stages, namely Research, Design, Planning, Coordination and Evaluation. The stages contained in the event management of the Pasa Harau Art & Culture Festival are as follows: 1) Research, this festival research carried out by several people who are members of the Culture-based Festival community, 2) The event design is based on the cultural richness and natural beauty of Nagari Harau, 3) Planning, this stage for Pasa Harau Festival starts one year before the Pasa Harau event is held, 4) Coordination involves the stakeholders and internal organizing committee, and 5) Evaluation discusses event reporting, event monitoring and evaluation of the whole event.